HADIS PREDIKTIF DALAM KITAB AL-BUKHARI - Idris, Abdul Fattah (Jurnal THEOLOGIA, 2013)
Abstract: This study of predictive hadith in the book al-BukhÄrÄ« give results; first, that all the predictive sanad are sÄ«ngle transmission (aá¸¥ad). The predictive hadith through sÄ«ngle transmission cannot be credible when it occurs tadlÄ«s, suspicion and ghaira ittiá¹£Äl (not continued). Second, the predictive of matan hadith is a tradition which should not be leaned by the Prophet. However, it is learned by the companions of the Prophet. Is name is mauquf hadith, If is leaned by tabi'in or itba' tabi'in generation, it is called a maqtuâ€™. The state of validity in matan predictive Hadith, depends on the state of the validity in sanad of Hadith. The state of avoiding disability (â€˜illat) of hadith sanad, is very decisive against the state on the validity of hadith matan, However, the state of validity on the hadith sanad is not necessarily a validity on the hadith matan. Therefore, some of predictive of hadith in book of Sahih al-Bukhari found disability in sanad of Hadith and in matan of hadith. In short, the direct or indirect predictive hadith in the the book of al-BukhÄrÄ« has disability ('illat), because it contains the contrary to the Qur'an, a political nature, and theological and dogmatic feud. Abstrak: Studi terhadap hadis prediktif dalam kitab al-BukhÄrÄ« ini memberi tiga hasil; pertama bahwa semua sanad predikif itu merupakan transmisi tunggal (aá¸¥ad). Hadis prediktif melalu transmisi tunggal tidak kredibel ketika terjadi tadlÄ«s, kecurigaan, dan ghaira ittiá¹£Äl (tidak bersambung). Kedua, bahwa matan hadis prediksi sebuah hadis yang seharusnya tidak di-marfuâ€˜-kan kepada Nabi, tetapi merupakan hadis mauquf yang disandarkan kepada sahabat, dan maqtuâ€˜ yang disandarkan kepada tÄbiâ€˜Ä«n atau itbaâ€˜tÄbiâ€˜Ä«n. keadaan kredibilitas matan hadis prediksi, tergantung pada keadaan kriteria sanad hadis. Kriteria terhindar dari â€˜illat (cacat) pada sanad hadis adalah sangat menentukan terhadap keadaan kredibilitas matan hadis, tetapi keadaan kredibilitas pada sanad hadis tidak serta merta menjadi kredibilitas pada matan hadis. Sebagian matan hadis prediktif dalam kitab á¹¢aá¸¥Ä«á¸¥ al-BukhÄrÄ« mempunyai â€˜illat dalam sanad hadis dan â€˜illat dalam matan hadis. Matan hadis-hadis prediksi yang diteliti baik secara langsung maupun tidak langsung adalah mengandung â€˜illat karena bertentangan dengan al-Quran, mengandung hal-hal yang bersifat politis, serta mengandung pertentangan teologis dan dogmatis. Keywrods: Hadis, Sunnah, Kriteria, Sanad, Matan, dan Prediktif